N-(4-Methoxybenzoyl)-N′-(4-methoxyphenyl)-thiourea - Ali, Hapipah Mohd; Ng, S.W.; Basirun, Wan Jefrey; Halim, S.N.A. (International Union of Crystallography, 2005)
Molecules of the title compound, C16H16N 2O3S, are linked by N-H⋯S hydrogen bonds to form centrosymmetric dimers [N⋯S = 3.4501 (13) Å]. The N′-phenyl and N-phenyl rings are twisted by 52.7(1) and 23.3(1)°, respectively, from the essentially planar -NHC(=S)NC(=O)- moiety. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.